Remote long-term registrations of sleep-wake rhythms, core body temperature and activity in marmoset monkeys - Hoffmann, Kerstin; Coolen, Alex; Schlumbohm, Christina; Meerlo, Peter; Fuchs, Eberhard (Behavioural brain research, 2012)
► The NeuroLogger® enables long-term recordings of sleep and activity in marmosets. ► The Remo200 system allowed for long-term measurement of core body temperature. ► Methods allow simultaneous registration of unrestrained pair-housed marmosets. ► Sleep deprivation leads to a homeostatic sleep rebound in marmosets. ► The marmoset is an interesting model for sleep and circadian research. Initial studies in the day active marmoset monkey (Callithrix jacchus) indicate that the sleep-wake cycle of these non-human primates resembles that of humans and therefore conceivably represent an appropriate model for human sleep. The methods currently employed for sleep studies in marmosets are limited. The objective of this study was to employ and validate the use of specific remote monitoring system technologies that enable accurate long-term recordings of sleep-wake rhythms and the closely related rhythms of core body temperature (CBT) and locomotor activity in unrestrained group-housed marmosets. Additionally, a pilot sleep deprivation (SD) study was performed to test the recording systems in an applied experimental setup. Our results show that marmosets typically exhibit a monophasic sleep pattern with cyclical alternations between NREM and REM sleep. CBT displays a pronounced daily rhythm and locomotor activity is primarily restricted to the light phase. SD caused an immediate increase in NREM sleep time and EEG slow-wave activity as well as a delayed REM sleep rebound that did not fully compensate for REM sleep that had been lost during SD. In conclusion, the combination of two innovative technical approaches allows for simultaneous measurements of CBT, sleep cycles and activity in multiple subjects. The employment of these systems represents a significant refinement in terms of animal welfare and will enable many future applications and longitudinal studies of circadian rhythms in marmosets.